LEGAL IMPLICATIONS ON THE MOVING OF THE STATE CAPITAL TO EAST KALIMANTAN - THAMRIN, HUSNI (Awang Long Law Review, 2020)
This paper aims to analyze the relationship between moving the state's capital city and regional government, and the legal implications of moving the state's capital city to East Kalimantan. This type of research is normative using a statutory approach and a conceptual approach. The data used is secondary data obtained through library research. All data collected were then analyzed qualitatively. The results show that the relationship between moving the state's capital city and regional government is the implementation of regional government which according to the Law of the Republic of Indonesia Number 23 Year 2014 concerning Regional Government regulates 9 (nine) aspects, namely: Central and Regional Government Relations, Regional Government Administration, Government Affairs, the Role of the Governor as Representative of the Central Government in the Regions, Regional Planning, Regional Apparatus, Regional Finance, Regional Regulations, and Regional Innovation. The legal implications of relocating the country's capital city to East Kalimantan include integration of settlement functions, education centers, research centers, service industrial areas, and recreation as well as being supported by adequate transportation systems, settlement infrastructure and city facilities (Revised Law No. 29 Year 2007 concerning the National Capital), has a strong city management concept and is able to control the utilization of city spaces and its territory effectively (Implementation of the Spatial Planning Law Number 26 Year 2007), has an integrated inter-modal public transportation system and integrated with city activity centers based on the concept of TOD (Transit Oriented Development), having a ready-to-build area and a ready-to-build environment (Implementation of Law Number 4 Year 1992 and Government Regulation Number 80 Year 1999), and capacity building and institutional development (capacity building and institutional development) management of the capital of the Unitary State of the Republic of Indonesia.